INTERACTIVE TEACHING METHODS IN ENGLISH LANGUAGE LESSONS (American Journal of Interdisciplinary Research and Development, 2022)
The article deals with one of the ways to modernize education on a competence - based basis, namely, through the use of interactive forms of education in teaching. Interactive teaching methods provide solutions to educational problems in various aspects. Possession of interactive learning technology contributes to the development of students' qualities that meet the requirements prescribed in the state standards of the new generation.